The 150th anniversary of the first depiction of the lesions of multiple sclerosis. Issue 10 (October 1988) - Compston, A
Abstract : The clinical and pathological features of multiple sclerosis were fully described, in France and subsequently in England, during the latter half of the XIXth century but clinical descriptions, personal accounts and depictions of the disease had appeared at various times over the previous 50 years. Jean Cruveilhier is usually credited with having first illustrated the lesions of multiple sclerosis in the second tome of his pathological atlas which bears the title date 1835. But the 40 livraisons which make up this work were published separately in parts and documentary evidence contained within the second volume indicates that the putative case of multiple sclerosis cannot have appeared earlier than 1841. Robert Carswell also may have published his pathological atlas in parts but the work was completed by 1838 and so his depiction of the lesions of multiple sclerosis, appearing on plate 4 fig 1, predates Cruveilhier's by at least three years. Curiously, Carswell and Cruveilhier each observed their pathological material in Paris but they cannot have depicted the same individual. 1988 is therefore the 150th anniversary of the depiction of the lesions of multiple sclerosis; the unnamed patient was French, the illustrator a Scotsman.